Спуфінг-атаки на біометричні системи автентифікації та методи протидії атакам - Кустов, А. К. (ХНУРЕ, 2020)
Biometric technologies are not completely protected from spoofing attacks. Survival detection methods are the most commonly discussed anti-spoofing measures. Survival detection is one of the important procedures in the registration, verification and identification processes. Therefore, it must be considered as an integral component of the biometric system. In this study raises an important issue of user authentication and protection of its data from spoofing attacks. In addition, the definition of spoofing attack is given. The types of spoofing attacks and methods for countering spoofing attacks are described using the example of a biometric face recognition system.
Keywords: спуфінг-атака; біометрична система; коефіцієнт помилки